(untitled) (The Agriculturists, 2018)
Field experiment was conducted at the farmers’ field of Amratoli, Barura multi location testing site of Cumilla during 2014-15 and 2015-16 to increase cropping intensity and productivity by inclusion of T. Aus in existing cropping pattern. Thus experiment variables were F: Existing cropping pattern (Potato -Boro-Fallow-T. Aman) and FA: Alternate cropping pattern (Potato- Boro- T. Aus- T.Aman). Research result indicated that rice equivalent yield (REY) in alternate cropping pattern was 43.46 t ha-1, which is 25.90% higher over existing pattern (34.52 t ha-1). Higher gross return (Tk. 651900 ha-1), gross margin (Tk. 416520 ha-1) and higher marginal benefit cost ratio (2.77) obtained from alternate cropping pattern messaged that this pattern may be recommended to other extrapolation areas of Cumilla region. The Agriculturists 2018; 16(2) 88-92